2020
DOI: 10.1038/s41467-020-19024-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social distancing and isolation on epidemic spreading modeled via dynamical density functional theory

Abstract: For preventing the spread of epidemics such as the coronavirus disease COVID-19, social distancing and the isolation of infected persons are crucial. However, existing reaction-diffusion equations for epidemic spreading are incapable of describing these effects. In this work, we present an extended model for disease spread based on combining a susceptible-infected-recovered model with a dynamical density functional theory where social distancing and isolation of infected persons are explicitly taken into accou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 91 publications
(89 reference statements)
4
63
0
2
Order By: Relevance
“…In Verachi et al (2020), the SIR model is used to evaluate the cost of management strategy. In Vrugt et al (2020), an SIR mathematical model with a dynamical density function is used for the spread of disease. In , a stochastic SIR mathematical model for a COVID-19 is developed to find the spread of the disease controlling value.…”
Section: Literature Survey On Mathematical Modelsmentioning
confidence: 99%
“…In Verachi et al (2020), the SIR model is used to evaluate the cost of management strategy. In Vrugt et al (2020), an SIR mathematical model with a dynamical density function is used for the spread of disease. In , a stochastic SIR mathematical model for a COVID-19 is developed to find the spread of the disease controlling value.…”
Section: Literature Survey On Mathematical Modelsmentioning
confidence: 99%
“…A similar connection with the basic SIR model has been recently introduced in Ref. (18) by using a generalised diffusion equation, also referred to as dynamical-density functional theory DDFT. This work could be nicely extended by coupling the basic DDFT equation with our controlled SIR model.…”
mentioning
confidence: 93%
“…In parallel, studies aiming to determine the virus dynamics, its geographical distribution and the peaks of the pandemic in given regions are necessary and useful for correct planning of immediate actions by states management. In this direction, several attempts to model the spread of the virus have been conducted recently [7, 6, 5, 9, 10, 11], including machine learning approaches [12]. Nonetheless, based on reports of these works that were more closely analyzed [5, 7, 6, 12], we found that many of these methods rely on parameters that are dependent on the advance of the spreading and on the regional context.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, studies aiming to determine the virus dynamics, its geographical distribution and the peaks of the pandemic in given regions are necessary and useful for correct planning of immediate actions by states management. In this direction, several attempts to model the spread of the virus have been conducted recently [7,6,5,9,10,11], including machine learning approaches [12].…”
Section: Introductionmentioning
confidence: 99%